The formation of halogen-specific TOX from chlorination and chloramination of natural organic matter isolates - Kristiana, Ina; Gallard, H.; Joll, Cynthia; Croue, J. (Elsevier Science Ltd, 2009)
The formation of disinfection by-products (DBPS) is a public health concern. An important way to evaluate the presence of DBPs is in terms of the total organic halogen (TOX), which can be further specified into total organic chlorine (TOCl), bromine (TOBr), and iodine (TOI). The formation and distribution of halogen-specific TOX during chlorination and chloramination of natural organic matter (NOM) isolates in the presence of bromide and iodide ions were studied. As expected, chloramination produced significantly less TOX than chlorination. TOM was the dominant species formed in both chlorination and chloramination. TOI was always produced in chloramination, but not in chlorination when high chlorine dose was used, due to the limited presence of HOI in chlorination as a result of the oxidation of iodide to iodate in the presence of excess chlorine. The formation of TOI during chloramination increased as the initial iodide ion concentration increased, with a maximum of similar to 60% of the initial iodide ion becoming incorporated into NOM. Iodine incorporation in NOM was consistently higher than bromine incorporation, demonstrating that the competitive reactions between bromine and iodine species in chloramination favoured the formation of HOI and thus TOI, rather than TOBr. Correlations between the aromatic character of the NOM isolates (SUVA(254) and % aromatic C) and the concentrations of overall TOX and halogen-specific TOX in chloramination were observed. This indicates that the aromatic moieties in NOM, as indicated by SUVA(254) and % aromatic C, play an important role in the formation of overall TOX and halogen-specific TOX in chloramination. THMs comprised only a fraction of TOX, up to 7% in chloramination and up to 47% in chlorination. Although chloramine produces less TOX than chlorine, it formed proportionally more non-THM DBPs than chlorine. These non-THM DBPs are mostly unknown, corresponding to unknown health risks. Considering the higher potential for formation of iodinated DBPs and unknown DBPs associated with the use of chloramine, water utilities need to carefully balance the risks and benefits of using chloramine as an alternative disinfectant to chlorine in order to satisfy guideline values for THMs.